Myxoma of the mitral valve - Antônio Sérgio C. Rocha; Maria Elizabeth Ferreira; Paulo R. Dutra; Nazareth N. Rocha; Solange M. Tinoco; Cesar Nascimento; Rosana Grandelle; Rita C. Villela; Marialda Coimbra; Celso Garcia (Arquivos Brasileiros de Cardiologia, 1999)
Only rarely do myxomas originate from the mitral valve. This is the report of a 49-year-old woman presenting with congestive heart failure. The diagnosis of an intracardiac tumor involving the anterior cuspid of the mitral valve was made by transesophageal echocardiography. The patient underwent surgery for tumor resection and plasty of the valve was made with reconstruction and preservation of the valve. The diagnosis of myxoma was confirmed by histology. This is the 23rd case of myxoma of the mitral valve reported in the literature.